Copper-instigated modulatory cell mortality mechanisms and progress in oncological treatment investigations - Gao, Lei; Zhang, Anqi (Frontiers in Immunology, 2023)
Copper, a transition metal, serves as an essential co-factor in numerous enzymatic active sites and constitutes a vital trace element in the human body, participating in crucial life-sustaining activities such as energy metabolism, antioxidation, coagulation, neurotransmitter synthesis, iron metabolism, and tetramer deposition. Maintaining the equilibrium of copper ions within biological systems is of paramount importance in the prevention of atherosclerosis and associated cardiovascular diseases. Copper induces cellular demise through diverse mechanisms, encompassing reactive oxygen species responses, apoptosis, necrosis, pyroptosis, and mitochondrial dysfunction. Recent research has identified and dubbed a novel regulatory cell death modality—"cuprotosis"—wherein copper ions bind to acylated proteins in the tricarboxylic acid cycle of mitochondrial respiration, resulting in protein aggregation, subsequent downregulation of iron-sulfur cluster protein expression, induction of proteotoxic stress, and eventual cell death. Scholars have synthesized copper complexes by combining copper ions with various ligands, exploring their significance and applications in cancer therapy. This review comprehensively examines the multiple pathways of copper metabolism, copper-induced regulatory cell death, and the current status of copper complexes in cancer treatment.